2010
DOI: 10.1053/j.gastro.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered Macrophage Function Contributes to Colitis in Mice Defective in the Phosphoinositide-3 Kinase Subunit p110δ

Abstract: Background and Aims-Innate immune responses are crucial for host defense against pathogens, but need to be tightly regulated to prevent chronic inflammation. Initial characterization of mice with a targeted inactivating mutation in the p110d subunit of phosphoinositide 3-kinase (PI3K p110δ D910A/D910A ) reveal defects in B-and T-cell signaling and chronic colitis. Here, we further characterize features of inflammatory bowel diseases (IBD) in these mice and investigate underlying innate immune defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 34 publications
5
87
2
Order By: Relevance
“…In p110δ D910A/ D910A mice, macrophages are hyperresponsive to TLR singaling and the augmented TLR signaling pathways elicits an exuberant inflammatory response. 25 Besides, the direct inhibition of Akt in monocytes resulted in a proinflammtory phenotype similar to that observed with PI3K inhibition. 26 Therefore, we hypothesized that inactivation of PI3Kδ/Akt signaling in macrophages play a crucial role in AAA development.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…In p110δ D910A/ D910A mice, macrophages are hyperresponsive to TLR singaling and the augmented TLR signaling pathways elicits an exuberant inflammatory response. 25 Besides, the direct inhibition of Akt in monocytes resulted in a proinflammtory phenotype similar to that observed with PI3K inhibition. 26 Therefore, we hypothesized that inactivation of PI3Kδ/Akt signaling in macrophages play a crucial role in AAA development.…”
mentioning
confidence: 62%
“…In p110δ D910A/ D910A mice, macrophages are hyperresponsive to TLR singaling and the augmented TLR signaling pathways elicits an exuberant inflammatory response. 25 Besides, the direct inhibition of Akt in monocytes resulted in a proinflammtory phenotype similar to that observed with PI3K inhibition.26 Therefore, we hypothesized that inactivation of PI3Kδ/Akt signaling in macrophages play a crucial role in AAA development.To test this hypothesis, we investigated the effect of PI3Kδ inactivation on artery architecture and AAA development in 2 distinct murine models in p110δ D910A/D910A mice and in vitro experiments with macrophage migration and MMPs expression. Our results suggested that MMP-12 is the most important molecules influenced by p110δ inactivation in arteries and in vascular injury models.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…It it is considered an excellent potential therapeutic target for reducing inflammation both in the acute allergic context but also in the context of chronic inflammatory disorders Rommel et al, 2007). The importance of p110delta in the regulation of inflammatory responses is highlighted by the development of spontaneous chronic colonic inflammation in the p110delta D910A/D910A mice, which has been attributed to a failure to repress inflammatory responses to commensal bacteria in the gut (Uno et al, 2010). Thus p110delta-selective drugs are currently under investigation as a treatment for rheumatoid arthritis, asthma and other inflammatory conditions.…”
Section: Chronic Inflammatory Conditionsmentioning
confidence: 99%